Pancreatico-Pleural and Bronchial Fistulae and Associated Pseudocysts: Case Series - Pandey, Salil; Shetty, Shiran A; Janarthanan, Krishnaveni; Balalakshmoji, Devanand; Sen, Kamal K; Leelakrishnan, Venkat (JOP. Journal of the Pancreas, 2014)
Context Pancreatico-pleural fistula is rare complication of chronic or acute pancreatitis. Previous studies have reported imaging features and various management options of this condition including conservative/medical management, endoscopic treatments and surgery.This article reviews the myriad of imaging appearances of this condition in multimodality imaging and different strategies for the successful management in a short case series. Methods After obtaining the institutional ethics committee approval, retrospective review of the medical records of five patients of pancreatico-pleural fistulae who were diagnosed and successfully managed in our hospital in 2012 and 2013 was done. Follow up with out patient records of these patients was also included.Findings were compared with the current available literature on this entity. Results and discussion Pancreatico-pleural fistulae presents with massive pleural effusion.A high index of suspicion is essential for accurate diagnosis. Demonstration of the fistulous tracts requires cross sectional imaging with contrast enhanced CT being most commonly used and affords accurate diagnosis. MRI demonstrates the tracts and ductal disruptions with greater detail and are helpful in confirming the CT findings. Endoscopic ultrasound and ERCP also offer potential of diagnosis, although being technically demanding and invasive is reserved for interventions. Management of these conditions should be initially conservative with endoscopic stenting being offered in selected cases with favourable anatomy and not responding to conservative management. Surgery is reserved for cases not responding to conservative and endoscopic management. Conclusion In conclusion this case series highlights the clinical and imaging spectrum of pancreatico-pleural fistulae and provides insight into the different management strategies that can be adopted for this condition. Image: Expansion of the fistulous tract at CT.